ENHANCING IMMERSIVE ENGLISH LEARNING THROUGH ARTIFICIAL INTELLIGENCE IN VIRTUAL AND AUGMENTED REALITY ENVIRONMENTS (Journal of Multidisciplinary Sciences and Innovations, 2025)
The integration of Artificial Intelligence (AI) into Virtual Reality (VR) and Augmented Reality (AR) technologies presents a transformative opportunity for English language education. Immersive environments powered by AI enable learners to experience real-time, context-rich language practice that closely mirrors real-world situations. This paper explores how AI-enhanced VR/AR tools can improve learners' linguistic competence, motivation, and retention. Drawing on recent technological developments and pedagogical theories, the study outlines the mechanisms by which AI personalizes interaction within immersive spaces and assesses the benefits and challenges associated with its implementation. The findings suggest that combining AI with VR/AR environments not only enhances communicative competence but also fosters learner autonomy and deep engagement, making it a promising model for future language learning paradigms.